2021
DOI: 10.1097/mpg.0000000000003279
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Ewing Sarcoma

Abstract: We report the youngest case of a patient with ulcerative colitis (UC) and primary sclerosing cholangitis (PSC) with Menetrier disease (MD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A brief search of PubMed revealed that only 55 cases of GI ES had been reported in the literature, most of which were single case reports. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] To date, no systematic study has been performed to investigate the clinical and pathologic characteristics of GI ES. The purpose of this study is to summarize the clinical and pathologic features of GI ES by reporting a series of 25 cases with a review of the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A brief search of PubMed revealed that only 55 cases of GI ES had been reported in the literature, most of which were single case reports. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] To date, no systematic study has been performed to investigate the clinical and pathologic characteristics of GI ES. The purpose of this study is to summarize the clinical and pathologic features of GI ES by reporting a series of 25 cases with a review of the literature.…”
Section: Discussionmentioning
confidence: 99%
“…A brief search of PubMed revealed that only 55 cases of GI ES had been reported in the literature, most of which were single case reports 2–17 . To date, no systematic study has been performed to investigate the clinical and pathologic characteristics of GI ES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation